Segmentation Using the Situational Theory of Publics: Breast Cancer Publics in Turkey - Esra Bozkanat; Ayla Okay (Türkiye İletişim Araştırmaları Dergisi)
This study aims to segment the breast cancer publics in Turkey based on their communicationbehavior. In addition to this purpose, the study seeks to identify reason-based behaviors that may affectcommunication behavior. Based on the Situational Theory of Publics (STP) and the Theory of ReasonedAction (TRA) as research models, this study analyses how the attitudes, intentions, and subjective normsof female participants towards breast cancer affect their active communication behavior. In terms ofmethodology, a questionnaire was carried out to measure breast cancer publics’ communicative behaviorin Turkey by eventually obtaining data for 500 valid and complete questionnaires. A cluster analysisidentified three breast cancer public types to exist in Turkey: Indifferent (n = 191), Conscientious (n =144), and Moderate (n = 159). As a result, combining STP with TRA was found to be a valid model insegmenting breast cancer publics in Turkey. This article further analyzed that subjective norms are thestrongest predictor of health behavior.